Cardiovascular events in patients undergoing hip fracture surgery treated with remote ischaemic preconditioning: 1‐year follow‐up of a randomised clinical trial. (13th January 2021) - Ekeloef, S.; Koyuncu, S.; Holst‐Knudsen, J.; Gundel, O.; Meyhoff, C. S.; Homilius, M.; Stilling, M.; Ekeloef, P.; Münster, A. M. B.; Mathiesen, O.; Gögenur, I.
Summary: Remote ischaemic preconditioning reduces the risk of myocardial injury within 4 days of hip fracture surgery. We aimed to investigate the effect of remote ischaemic preconditioning on the incidence of major adverse cardiovascular events 1 year after hip fracture surgery. We performed a phase‐2, multicentre, randomised, observer‐blinded, clinical trial between February 2015 and September 2017. We studied patients aged ≥ 45 years with a hip fracture and a minimum of one cardiovascular risk factor. Patients were allocated randomly to remote ischaemic preconditioning applied just before surgery or no treatment (control group). Remote ischaemic preconditioning was performed on the upper arm with a tourniquet in four cycles of 5 min ischaemia and 5 min reperfusion. Primary outcome was the occurrence of major adverse cardiovascular events within 1 year of surgery. A total of 316 patients were allocated randomly to the remote ischaemic preconditioning group and 309 patients to the control group. Major adverse cardiovascular events occurred in 43 patients (13.6%) in the remote ischaemic preconditioning group compared with 51 patients (16.5%) in the control group (adjusted hazard ratio (95%CI) 0.83 (0.55–1.25); p = 0.37). Fewer patients in the remote ischaemic preconditioning group had a myocardial infarction (11 (3.5%) vs. 22 (7.1%); hazard ratio (95%CI) 0.48 (CI 0.23–1.00); p = 0.04). Remote ischaemic preconditioning did not reduce the occurrence of major adverse cardiovascular events within 1 year of hip fracture surgery. The effect of remote ischaemic preconditioning on clinical cardiovascular outcomes in non‐cardiac surgery needs confirmation in appropriately powered randomised clinical trials.